Benefit of Radiotherapy in Extraskeletal Myxoid Chondrosarcoma: A Propensity Score Weighted Population-based Analysis of the SEER Database. (July 2018) - Kemmerer, Eric J.; Gleeson, Elizabeth; Poli, Jaganmohan; Ownbey, Robert T.; Brady, Luther W.; Bowne, Wilbur B.
Abstract : Objectives: Extraskeletal myxoid chondrosarcoma (EMC) is a rare malignancy for which the role of radiotherapy is not well-defined. We examine the effect of external beam radiotherapy (EBRT) on cancer-specific survival (CSS) for patients with localized EMC, in a propensity score weighted, population-based analysis. Materials and Methods: The Surveillance, Epidemiology, and End Results database (1973 to 2012) was queried for cases of localized EMC arising from soft connective tissues of the trunk and extremities treated with surgery and/or EBRT. Inverse probability treatment weighting was utilized, with survival analysis by weighted Cox regression and Kaplan-Meier analysis with log-rank testing. The primary endpoint was CSS. Results: One hundred seventy-two patients were identified, diagnosed from 2004 to 2012. Ninety-four percent and 32% of 156 assessable patients underwent surgery and EBRT, respectively. By inverse probability treatment weighting, balancing covariates of age group, sex, race, grade, T stage, N stage, receipt of surgery, and anatomic site, we observed CSS of 97% versus 85% and 94% versus 85% in patients receiving EBRT versus no EBRT, at 3 and 5 years, respectively, at median follow-up of 33 months, P =0.01. A trend toward an overall survival benefit associated with EBRT was noted, P =0.06. Further adjusting for type of resection performed, CSS benefit persisted, 97% versus 85% at 3 years and 94% versus 85% at 5 years, P =0.02, with trend toward an overall survival benefit, P =0.08. Conclusions: The receipt of EBRT is associated with a CSS benefit in localized EMC. Aggressive local therapy, including EBRT, should be considered in these patients. Abstract : Supplemental Digital Content is available in the text.